A multitasking multi-objective differential evolution gene selection algorithm enhanced with new elite and guidance strategies for tumor identification - Li, Min; Zhao, Yangfan; Lou, Mingzhu; Deng, Shaobo; Wang, Lei (Expert systems with applications, 2024)
•MMODE is developed as a new hybrid gene selection method for tumor identification.•MMODE combines multi-tasking and multi-objective frameworks.•MMODE uses a new elite strategy and a new guidance strategy.•MMODE selects a few genes and achieves high classification accuracy. A key preprocessing step in tumor recognition based on microarray expression profile data and machine learning is to identify tumor marker genes. Gene selection aims to select the most relevant gene subset from the original ultra-high dimensional microarray expression profile data to improve tumor identification performance. Inspired by evolutionary multitasking (EMT) and multi-objective optimization, this paper puts forward a novel multitasking multi-objective differential evolution gene selection algorithm (MMODE) which uses new elite and guidance strategies to select the best gene subsets. MMODE initializes two different populations according to different filtering criteria to increase the diversity of the search. These two populations guide their respective populations to search in the optimal direction through knowledge transfer in the evolutionary process. In addition, MMODE employs new elite and guidance strategies that enables individuals to narrow the search range and jump out of local optima. The proposed algorithm is validated on 13 publicly available microarray expression datasets in comparison with state-of-the-art gene selection algorithms. The experimental results show that MMODE can find smaller gene subsets and achieve higher classification accuracy compared with other algorithms.